Overview of the agricultural input sector in Ghana - Krausova, Marika; Banful, Afua Branoah (International Food Policy Research Institute, 2010)
Knowledge of the characteristics and size of the agricultural input sector of a country is critical for policymakers to design appropriate interventions that not only foster growth in the sector, but also support the agricultural development goals of the country. In 2009, the International Food Policy Research Institute and the International Fertilizer Development Center jointly conducted a census of agricultural input dealers in Ghana to fill a critical data gap on the nature of the country's agricultural input sector. This paper presents a detailed description of the sector's structure, market practices, and supply chain. It also assesses the sector's response to recently implemented fertilizer subsidies, and findings show that, despite the government's goal of making the subsidy program supportive of the private market, the majority of fertilizer retailers were excluded from participating.